1987
DOI: 10.1002/pen.760271109
|View full text |Cite
|
Sign up to set email alerts
|

Tensile yield in polypropylene

Abstract: Untaxial tension tests to the yield point were performed on polypropylene as a function of temperature from 22 to 143°C at a strain rate of 2 min−1. At 22, 42, and 71°C, measurements were also made at strain rates from 0.02 to 8 min−1. Yield energy was found to be a linear function of temperature extrapolating to zero at the melting point (164°C). The ratio of thermal to mechanical energy to produce yielding is about three times smaller than for glassy polymers. The ratio of yield stress to (initial) Young's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 14 publications
6
14
0
1
Order By: Relevance
“…Mechanical properties of PP were studied in tension at room and elevated temperatures (25,40,70, 100 o C) using an Instron tensile testing machine equipped with the environmental chamber. Samples before the test were conditioned at least 15 min at the drawing temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical properties of PP were studied in tension at room and elevated temperatures (25,40,70, 100 o C) using an Instron tensile testing machine equipped with the environmental chamber. Samples before the test were conditioned at least 15 min at the drawing temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the increase of drawing temperature influences the mechanical properties, among them a macroscopic yield 25 . The yield stress decreases with the increase of the temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also generally accepted that stress‐induced fragmentation and recrystallization process would take place readily with increasing deformation temperature . Besides, the study of drawing behavior of polyethylene by Hartmann et al has shown that, the yield strain reaches a maximum value at the temperature of deformation around 60–70 °C and yield stress decreases with the increase of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of this standard and directions for its improvement include laboratory tests dealing with function, wear and tear, and environmental influences. Because there are no standards for such tests, appropriate procedures will need to be ~pecified.~ A number of aspects relevant to an understanding of tensile behavior under accelerated environmental conditions have been investigated (1) effect of polymer structure on the tensile behavioq6-13 (2) effect of processing on structural degradati~n;~~,''~'~ definitions and values of tensile strength for thermoplastic polymers with strain rates not always specified;7-8,10, [15][16][17][18][19][20][21][22] and (6) artificial eath he ring. ".^^-^^,^^ In addition, limited statistical a n a l y s e~'~J~-~~.~~ and rankings development19~20~22 have been published.…”
mentioning
confidence: 99%